The Clitics in Standard Lithuanian - Kazlauskienė, Asta (Respectus Philologicus, 2015)
A Lithuanian word is quite an autonomous prosodic unit. Nevertheless, in some cases a word loses stress, connects to an adjacent word, and becomes a part of a succeeding or preceding word. The aim of this research is to establish and describe the prosodic autonomy of the Lithuanian language word and its determinants.The database for this analysis consists of some audio recordings of novels, which were used in this study (11 h 20 min, 22 speakers). A computational programme was designed by Prof. Dr. G. Raškinis.The empirical data showed that the words with clitics comprise about ¼ of all the words. The data analysis suggests that the word autonomy depends on many factors: phonetic structure (monosyllabic words often lose their stress), morphological features (uninflected parts of speech, especially prepositions, often do not have a stress), the structure of a sentence (a potential clitic can get a stress in an elliptic sentence), pragmatic intentions (a word with a phrase stress will get a lexical stress), and the pressure of the rhythm (a potential clitic can keep stress due to the succeeding unstressed syllable). The latter factor is important for the rhythm of the speech for two reasons. First, a clitic can eliminate a stress clash, which might be formed if both words had stresses. Second, if clitic is connected to the word with a first stressed syllable, the second syllable would become stressed. Such word is articulated easier than the word which begins with a stressed syllable. However, the rhythm does not have a major impact on the word autonomy in the Lithuanian language. The phonetic structure and morphological features have the most significant influence on the prosodic autonomy of a word.
Keywords: stress; clitics; rhythm; uninflected part of speech; morphological multiword units